Training on statistical applications in structuring village administration in Purworejo - Mustofa Usman; Edwin Russel; Lidya Ayuni Putri (Journal of Community Service and Empowerment, 2024)
In the modern era, statistics has become an integral part of various aspects of our lives, serving as a universal language to understand the world around us. The integration of statistical applications can significantly enhance the process of data and information management in village governance. This community service project aims to assess the potential of statistical applications in supporting village administration officials, contributing to improved village governance and self-sufficiency. Through preliminary studies and tailored SPSS training programs, the practical knowledge and skills of village officials and cooperative members are enhanced. Evaluation after the training indicates a significant improvement in understanding and application of statistical tools. The integration of statistical applications is expected to contribute to better-organized village administration and good governance in Purworejo Village. This initiative underscores the role of statistics as a powerful tool in village administration, bridging various fields of knowledge and providing valuable insights into the world. The successful implementation of statistical applications in Purworejo Village serves as a model for other communities seeking to enhance governance through data-driven decision-making.